Two new species of Fiorinia Targioni-Tozzetti (Hemiptera: Coccoidea: Diaspididae) from China - Wei, Jiufeng; Zhang, Bin; Feng, Jinian (Zootaxa, 2013)
The adult females of two new species of armored scale, Fiorinia tianshuiensis Wei & Feng sp. n. and F. dinghuensis Wei & Feng sp. n., are described and illustrated from specimens collected from China. A key is provided for the all Fiorinia species known from China.